Parental Control in Shaping Children’s Religios Character in Rural Communities: a Case Study of Balikbakhilir Hamlet - Kamaliyah, Fauzatul; M, Ansharuddin (STAI Syaichona Moh. Cholil Bangkalan, 2025)
The good and bad character of children depends a lot on how much the role of parents in educating them. School, teachers and society only help to complement and maximize the role of parents in the formation of children's character. Therefore, the purpose of this study is to present how parents' control in the formation of children's religious character. The descriptive qualitative method was used to describe the dynamics of the relationship between parents and children and identify best practices in educating children based on religious values. The results show that parents who are actively involved in their children's religious education can help shape a disciplined, empathetic and moral character, which is important for children's social and emotional development. This research emphasizes the importance of parents' role in providing consistent and balanced religious education and creating an environment that supports children's early spiritual development.